PEMBENTUKAN BRAND LOYALTY MELALUI REBRANDING DAN RATIONAL APPEALS - Dewi Zahrotul Munifa Dila (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2017)
In the competitive telecomunication industry, brand loyalty has become an important issue.Strong brand and marketing activity are becoming one of the critical levers for company’sdifferentiation and successed. The aim of this study is to find the impact of rebranding andrational appeals on brand loyalty development while using brand image as mediator in IndosatOoredoo. The sample consist of 100 respondent as Indosat Ooredoo consumer who live inSemarang. Through a structured questionnaire data were collected and with the help of SPSS,analysis was made.The results reveal that rational appeals and rebranding has significanteffects on brand image. Rebranding has no impact on brand loyalty, while Indosat Ooredoo’srational appeals and brand image has significant effect on building consumer’s brand loyalty.In the other side, rational appeals has directly impact on brand loyalty, while rebranding hasundirect impact on loyalty throuh brand image as mediator.Keywords: rebranding, rational appeals, brand image, brand loyalty